Pancasila Principle of Justice in the Regulation of (Conventional) Insurance Standard Contract in Indonesia - Christian, Andri (Global Legal Review, 2025)
The purpose of this research is to analyze the ideal regulation provide protection for the insured in the statutory provisions related to Indonesia’s conventional insurance standard contract in order to realize the Pancasila principle of justice. This research uses normative legal research methods, the application of which is rational theoretical, so the disclosure is tied to methods based on deductive logic requirements. The ideal regulations that can provide protection for the insured, carried out through the formation of regulations and implementing regulations, they are formed in stages and based on other norms in the series of legal systems. The objectives of the establishment include external and internal legal protection, as well as creating certain equality and restrictions to protect those with weaker bargaining positions. The regulations formed are applied simultaneously with supervisory measures, concrete sanctions, the content of regulations is formed from within the law and has an impact on society, and the values contained in the regulations are intrinsic Pancasila, which then the regulations are consistently obeyed by all parties. The intrinsic values of Pancasila are realized through the application of the Pancasila principle of justice in the regulation of conventional insurance standard contract in Indonesia by applying the Pancasila triangle of justice interrelation.